Rpl3l gene deletion in mice reduces heart weight over time - Grimes, Kelly M.; Prasad, Vikram; Huo, Jiuzhou; Kuwabara, Yasuhide; Vanhoutte, Davy; Baldwin, Tanya A.; Bowers, Stephanie L. K.; Johansen, Anne Katrine Z.; Sargent, Michelle A.; Lin, Suh-Chin J.; Molkentin, Jeffery D. (Frontiers in Physiology, 2023)
The ribosomal protein L3-like (RPL3L) is a heart and skeletal muscle-specific ribosomal protein and paralogue of the more ubiquitously expressed RPL3 protein. Mutations in the human RPL3L gene are linked to childhood cardiomyopathy and age-related atrial fibrillation, yet the function of RPL3L in the mammalian heart remains unknown. Here, we observed that mouse cardiac ventricles express RPL3 at birth, where it is gradually replaced by RPL3L in adulthood but re-expressed with induction of hypertrophy in adults. Rpl3l gene-deleted mice were generated to examine the role of this gene in the heart, although Rpl3l-/- mice showed no overt changes in cardiac structure or function at baseline or after pressure overload hypertrophy. RNA expression analysis and ribosome profiling failed to show differences between the hearts of Rpl3l null and wild type mice in adulthood. Moreover, ribosomes lacking RPL3L showed no differences in localization within cardiomyocytes compared to wild type controls, nor was there an alteration in cardiac tissue ultrastructure or mitochondrial function in adult Rpl3l-/- mice. Similarly, overexpression of either RPL3 or RPL3L with adeno-associated virus 9 in the hearts of mice did not cause discernable pathology. However, by 18 months of age Rpl3l-/- null mice had significantly smaller hearts compared to wild type littermates. Thus, deletion of Rpl3l forces maintenance of RPL3 expression within the heart that appears to fully compensate for the loss of RPL3L, although older Rpl3l-/- mice showed a mild but significant reduction in heart weight.